NEW STANDARD PRACTICE OF THE AIRPORT OPERATIONS FOR THAILAND DURING THE OUTBREAK OF CORONAVIRUS DISEASE 2019 (COVID-19) - Paethrangsi, Nisara; Jandaboue, Wanlapa; Teekasap, Sombat (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
Airlines and airports are experiencing an unprecedented challenge from the outbreak of Coronavirus Disease 2019. The research aims 1) to explore the practice of an airport operations during the COVID-19 pandemic, 2) to compare the views of passengers and frontline personnel on the new standard practice of airport operations, and 3) to propose the new standard procedures for airport operations. This study employed mixed methods, mainly a survey, supplemented by an in-depth interview for robustness. The sample comprised 150 frontline employees who work at the airport, including airline staff, airport workers, retail employees, and the personnel in service providers. Moreover, 150 customers have experience using the airports during the COVID-19 pandemic. Key findings and analyses revealed that the new standard practice for airport operations comprised four factors: technologies, environments, services, and operations. Hygiene environment and non-touch technologies such as using biometric solutions for border clearance, self-boarding passes, baggage scanners, and intelligent tags & RFID make passengers confident that the airport’s area is safe and free from coronavirus infection.